2018
DOI: 10.1016/j.pedneo.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art acute phase management of Kawasaki disease after 2017 scientific statement from the American Heart Association

Abstract: Kawasaki disease (KD) has become the most common form of pediatric systemic vasculitis. Although patients with KD received intravenous immunoglobulin (IVIG) therapy, coronary arterial lesions (CALs) still occurred in 5%-10% of these patients during the acute stage. CALs may persist and even progress to stenosis or obstruction. Therefore, CALs following KD are currently the leading cause of acquired heart diseases in children. The etiology of CALs remains unknown despite more than four decades of research. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Determining whether this observation is the result of increased diagnosis due to improved awareness and/or access to specialist medical services or reflective of an actual increase in incidence is difficult (15). Both factors likely play a role in many countries, particularly in those countries where KD has been described more recently (16).…”
Section: Discussionmentioning
confidence: 99%
“…Determining whether this observation is the result of increased diagnosis due to improved awareness and/or access to specialist medical services or reflective of an actual increase in incidence is difficult (15). Both factors likely play a role in many countries, particularly in those countries where KD has been described more recently (16).…”
Section: Discussionmentioning
confidence: 99%
“…We also used peripheral blood samples from KD patients before they underwent IVIG treatment (pre-IVIG) and then at least 3 days or 3 weeks after completing the IVIG treatment, as previously described in one of our previous studies 19. CAL was identified through echocardiography and defined as a coronary artery with an internal diameter of at least 3 mm (4 mm if the patient was more than 5 years old), a segment with an internal diameter at least 1.5 times larger than that of an adjacent segment, as 20, 21, or a Z score ≧ 2.5, and the severity of the coronary was classified using Z scores according to the 2017 AHA statement 22, 23. This study received approval from the Chang Gung Memorial Hospital's Institutional Review Board, and we also obtained written informed consent from the parents or guardians of all subjects.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of KD depends on the principal clinical features, evidence of systemic inflammation and echocardiographic findings of CAA 25 . Inflammatory mediators play a vital role in judging the disease activity, clinical classification, IVIG response and CAA risk.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 The diagnosis of KD depends on the principal clinical features, evidence of systemic inflammation and echocardiographic findings of CAA. 25 Inflammatory mediators play a vital role in judging the disease activity, clinical classification, IVIG response and CAA risk. In Korea, a retrospective study encompassing 795 KD patients by Ha et al 26 indicated that ANC was significantly higher in patients with CAA than in those without CAA, and CRP was significantly higher in complete KD patients than in incomplete KD patients.…”
Section: Nca and Ivig Therapymentioning
confidence: 99%